The role of bone scintigraphy with single-photon emission computed tomography-computed tomography in the diagnosis and evaluation of calciphylaxis - Patrick Martineau; Matthieu Pelletier-Galarneau; Sadri Bazarjani (World Journal of Nuclear Medicine)
Calciphylaxis, also known as calcific uremic arteriolopathy, is an uncommon disease, typically found in patients with the end-stage renal disease. Pathophysiological features include small vessel vasculopathy with mural calcification, fibrosis, and thrombosis. The clinical presentation varies but often consists of the necrosis of skin and subcutaneous tissues, with or without visceral organ involvement due to small vessel vasculopathy. This condition has a significant morbidity and mortality, making accurate diagnosis imperative. We present a case of calciphylaxis investigated using planar bone scintigraphy and single-photon emission computed tomography-computed tomography (SPECT-CT). This case stresses the value of SPECT-CT to accurately localize the abnormal uptake in subcutaneous soft tissue microcalcifications and confirms the exact location and extent of pathology.